A Conceptual Framework of Mobile Payment System Adoption and Use in Southeast Asia - Chang, Andreas; Gunawan, Theresia; Sumarwan, Ujang (JAS (Journal of ASEAN Studies), 2023)
The research aims to investigate the factors affecting consumers' adoption and use of Mobile Payment Systems (MPS) in Southeast Asia. Extant theoretical models need to be extended to cover the unique features of mobile payment technology. A Systematic Literature Review (SLR) is conducted to analyse theoretical models utilized to predict the adoption and use of mobile payment. A total of 60 studies about adoption and use of MPS is analysed. The results of the investigations employ the Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT), and Diffusion of Innovation model (IDT). It reveals that there are inconsistencies in determinants of behavioral intention to adopt and use MPS. Among them are performance expectancy, effort expectancy, and social influence. The review also unveils the use of other determinants to predict behavioral intention to adopt and use MPS, such as perceived security, perceived risks, perceived trust, attitude, and financial incentives to lure new users. The researchers propose a conceptual framework for MPS adoption and use that includes four moderators: gender, age, educational level, and income level. The research contributes to the theory and practice by explicating relevant factors predicting behavioral intention to adopt and use mobile payment in the ASEAN region.  Moreover, the SLR offers opportunities for future investigations.